Optimal distances between metro stations in centre dominated metropolitan areas - Piet Rietveld (European Regional Science Association (ERSA), 2004)
When the city centre is the major destination of the passengers, public transport vehicles will get fuller as they approach it. The disadvantage of time loss due to stops on the way to the centre is thus experienced by an increasing number of travellers. We demonstrate that optimal stop distances increase as vehicles get closer to the centre. This is at variance with the usual assumption of constant stop distances employed in this type of models. A Countervailing force is that urban densities increase as one approaches the centre. We demonstrate that there exist combinations of the various cost and density gradient parameters that result in constant stop distances as an optimal outcome. However, this is found for rather steep density gradients, so that the overall conclusion is that there are good reasons to let stop distances increase as one approaches the city centre. Keywords: Stop distance, public transport, density gradient, public transport access
Keywords: 330; Stop distance; public transport; density gradient; public transport access